INCREASING PUBLIC KNOWLEDGE ABOUT COVID-19 THROUGH DOOR TO DOOR CAMPAIGN - Depi Yulyanti; Wibin Pangestu; Dimas Diofani (Journal of Health Community Service, 2021)
Based on COVID-19 monitoring data from the Indramayu District Health Office, there were 210 additional confirmed cases of COVID-19 on June 20, 2021. This number was the highest daily confirmed cases during the pandemic in Indramayu Regency, the data still increase until now. Of the total number of 9,795 confirmed cases, 1,179 people were still being treated, 8,353 had recovered and 263 had died. Based on observations, it was known that there were still many people who did not comply with the health protocols regulation. Therefore, education was needed so that public knowledge about the signs, symptoms, prevention and reporting flow of COVID-19 cases able to increase. The target of the activity was the head of RT and RW in Pekandangan Jaya Village, Indramayu District, Indramayu Regency. This activity aimed to determine the public knowledge change before and after being given education about COVID-19. The method of implementation was door to door to RT and RW houses using educational media in the form of posters for 3 days from 14 to 16 July 2021, held every 10.00 to 15.00 WIB, knowledge measurement was carried out by giving pre and post test questions. The results of providing education were known to increase public knowledge about signs and symptoms, prevention efforts and the flow of COVID-19 case reporting by 19%. It is known that 56.2% before being given counselling and 75.2% after being given counselling. Further community service is needed to measure changes in community behavior in Pekandangan Jaya Village.